1986
DOI: 10.1242/jcs.1986.supplement_5.13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Of The Sea-Urchin Egg Microtubule-Activated Atpase

Abstract: SUMMARYWe have found that cytoplasmic extracts from unfertilized sea-urchin eggs contain a prominent microtubule-activated ATPase activity. This activity is induced by polymeric tubulin, but not by tubulin subunits. The activity cosediments with taxol-stabilized microtubules in an ATPindependent manner. We have separated the ATPase from cytoplasmic dynein and other ATPases on sucrose gradients. The sedimentation, enzymic and microtubule-binding properties of the microtubule-activated species show it to be dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is noteworthy that brain dynein, kinesin, and the 10S ATPase all have been reported to exhibit values of Kmt below 1.5 mg/ml tubulin (Fig. 1; Kuzentsov and Gelfand, 1986;Collins and Vallee, 1986b). Lye et al (1987) have reported the purification of a 20S…”
Section: Relationship Of the Brain Cytoplasmic Dynein To Other Microtmentioning
confidence: 98%
“…It is noteworthy that brain dynein, kinesin, and the 10S ATPase all have been reported to exhibit values of Kmt below 1.5 mg/ml tubulin (Fig. 1; Kuzentsov and Gelfand, 1986;Collins and Vallee, 1986b). Lye et al (1987) have reported the purification of a 20S…”
Section: Relationship Of the Brain Cytoplasmic Dynein To Other Microtmentioning
confidence: 98%
“…To address the question of assembly competence and specificity of association, we performed experiments using an alternative assembly/disassembly procedure to remove proteins that were not integral components of the microtubule lattice. This procedure is based on taxol stabilization of microtubules followed by a dissociative treatment with high salt to remove microtubule-associated proteins (Vallee, 1982;Collins & Vallee, 1986;Dinsmore & Sloboda, 1987). In these experiments, procaryotic synthesis reaction crudes were mixed with [3H]Tyr45l-tubulin (an internal positive control) and purified by anion-exchange chromatography.…”
Section: Methodsmentioning
confidence: 99%